Dinamika Ijtihad dan Bermadzhab dalam Islam dalam Perspektif Integrasi Ilmu Agama, Sosial, dan Hukum untuk Buku Fikih Kelas XII Bab II - Suyyirah, Suyyirah; Sholichin, M. Muchlis; Maysurah, Maysurah; Holis, Nor (Invention: Journal Research and Education Studies, 2025)
This article discusses the dynamics of ijtihad and school of thought in the development of Islamic law through an interdisciplinary approach that integrates religious, social, and legal aspects. Using qualitative methods with literature review, this study explores the importance of ijtihad that combines revelation, rationality, and critical philosophy in an open and inclusive manner. The results show the need to show the adaptation of ijtihad to socio-cultural changes and the importance of renewal in school of thought in order to answer the global challenges of the Muslim community.